Optimizing Natural Dyeing Processes to Improve Product Quality Ecoprint-Based Creative Industries that Support Sustainable Economic Growth - Sugiarto, Catur; Rahmawati, Rahmawati; Sawitri, Hunik Sri Runing; Santoso, Ratna Endah; Arifah, Siti; Amperawati, Endang Dwi; Saputra, Andreansyah; Akbar, Mi'raj; Shaikh, Junaid M (Jurnal IPTEK Bagi Masyarakat, 2026)
This community service activity aims to improve the product quality and business capacity of ecoprint MSMEs through the optimization of natural dyeing processes based on ketapang leaves (Terminalia catappa) and sappanwood (Caesalpinia sappan), integrated with strengthening business management and digital marketing. The implementation method employed a participatory approach through several stages, including socialization, training on natural dye extraction, practice of dyeing and color fixation, business management training, as well as monitoring and evaluation. The results indicate a significant improvement in the partners’ capacity. Optimization of the mordanting and fixation processes improved the color fastness of products from a low category to a moderate–high category based on washing and rubbing tests. Production efficiency also increased, as indicated by the reduction of production time from approximately seven days to four to five days per production cycle and an increase in production capacity of around 30%. In addition, product diversification of ecoprint products was achieved, resulting in various derivative products such as eco-tik, tote bags, and ready-to-wear clothing, along with increased digital marketing activities through social media and marketplaces. The novelty of this program lies in the integration of technical innovation in optimizing natural dyes with the empowerment of business management and digital marketing for creative MSMEs. This integrated approach has proven effective in improving product quality, production efficiency, and business competitiveness. The findings indicate that strengthening production capacity based on local resources, supported by business management and digital marketing, can serve as a sustainable empowerment model for creative MSMEs. This program contributes to the achievement of the Sustainable Development Goals (SDGs), particularly Goal 8, by increasing business productivity, expanding market access, and encouraging economic growth based on environmentally friendly creative industries.